2018
DOI: 10.1371/journal.pone.0208402
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perceptions and self-paid hepatitis B vaccination: A structural equation modeling approach

Abstract: BackgroundMalaysia has a comprehensive, publicly-funded immunization program for hepatitis B (HepB) among infants, but adults must pay for the vaccine. The number of HepB carriers among adults is expected to increase in the future; therefore, we examined the impact of five constructs (cues to action, perceived barriers, perceived benefit, perceived severity, and perceived susceptibility) on adults’ willingness to pay (WTP) for HepB vaccine; secondarily, we examined the association between perceived barriers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 29 publications
4
30
0
1
Order By: Relevance
“…One important finding is that those who had a higher perceived risk to be infected with COVID-19 were more likely to accept the vaccine, but only for the 95% effective vaccine. Previous studies in Asia have found that perceived risk or perceived susceptibility to an infection is associated with positive support for vaccination (29,30,39). Another study also found that high perceived risk was associated with COVID-19 vaccine acceptance among general community members in Saudi Arabia (40) and among HCWs in China (41).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…One important finding is that those who had a higher perceived risk to be infected with COVID-19 were more likely to accept the vaccine, but only for the 95% effective vaccine. Previous studies in Asia have found that perceived risk or perceived susceptibility to an infection is associated with positive support for vaccination (29,30,39). Another study also found that high perceived risk was associated with COVID-19 vaccine acceptance among general community members in Saudi Arabia (40) and among HCWs in China (41).…”
Section: Discussionmentioning
confidence: 86%
“…In the region of southeast Asia, studies have been conducted to assess the acceptance of a vaccine against infectious diseases (21)(22)(23)(24)(25)(26)34). This present study was conducted to understand how the COVID-19 vaccine, when available, will be accepted by the general population in Indonesia, by asking individuals about a hypothetical vaccine-an approach used in many past studies (21,26,(28)(29)(30). Understanding vaccine acceptance in Indonesia is important, given the large population and because the country has relatively high vaccine hesitancy for existing vaccines and relatively low vaccination coverage (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was part of the Malaysian Hepatitis B Project. [45][46][47] Selangor was chosen because it is the most populated state in Malaysia and has the highest number of households (Department of Statistic Malaysia, 2015). The protocol used in this study was approved by Universiti Putra Malaysia, Selangor, Malaysia.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…Based on the conservative assumption that 50% of participants would be at high risk for HepB, a 5% margin of error with a confidence interval of 95% and Selangor's population of 5.79 million people, 48 385 respondents were required for this study. However, because this study was part of Malaysian Hepatitis B Project [45][46][47] whose main objective was to assess the willingness-to-pay (WTP) for HepB vaccine, 45 the sample size was calculated to answer the main project's objective. Based on a formula from the literature, 49 the minimum sample size required was 683.…”
Section: Sampling Procedures and Sample Sizementioning
confidence: 99%